Analisis Pebandingan Kinerja Keuangan Pemerintah Daerah Kabupaten Sorong Dan Pemerintah Kota Sorong Periode 2012-2016 - Jumame, Farley (Universitas Sam Ratulangi, 2018)
The results show that there is a significant difference between sorong district government financial performance and sorong municipal government. Average value of independency ratio, effectiveness ration, efficiency ratio, routine spending total to APBD, total development spending sorong municipal better than sorong district government.Keywords: financial ratio, sorong district government, sorong municipal